2019
DOI: 10.3390/en12112038
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Air Density Using Observations and Re-Analysis Outputs for Wind Energy Purposes

Abstract: A method to estimate air density as a function of elevation for wind energy resource assessments is presented. The current practice of using nearby measurements of pressure and temperature is compared with a method that uses re-analysis data. It is found that using re-analysis data to estimate air density gives similar or smaller mean absolute errors compared to using measurements that were on average located 40 km away. A method to interpolate power curves that are valid for different air densities is present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…Given the great hub heights of modern turbines, these mesoscale models are interesting, because they give a good approximation of wind speed at these heights when vertical interpolation from the original η model levels is used. Anyway, Floors et al [37] have shown that air density should be also corrected. For instance, an air density reduction of 2% is expected according to their model for a turbine with a tower of 200 m. Therefore, in future studies about seasonal variations of air density this aspect of the hub height and the consequent reduction of air density should be introduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the great hub heights of modern turbines, these mesoscale models are interesting, because they give a good approximation of wind speed at these heights when vertical interpolation from the original η model levels is used. Anyway, Floors et al [37] have shown that air density should be also corrected. For instance, an air density reduction of 2% is expected according to their model for a turbine with a tower of 200 m. Therefore, in future studies about seasonal variations of air density this aspect of the hub height and the consequent reduction of air density should be introduced.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent work, Floors et al [37] mentioned the importance of air density in wind energy potential estimation, but in their case the subject consists in the reduction of air density at the hub height compared to air density obtained from measurements at lower levels. Additionally, they have found that using re-analysis data (ERA5 in their case) to estimate air density gives similar or smaller errors compared to using nearest measurements around the point of study.…”
Section: 2mentioning
confidence: 99%
“…ERA5 provides pressure, temperature and humidity at sea level which allows calculation of local air density. Most wind farm feasibility studies ignore the impact that air density changes have on wind energy production [9,10]. Instead, a constant value around 1.225 kg/m 3 (ρ 0 ) is assumed at sea level while at higher altitudes, their yearly averages are used.…”
Section: Introductionmentioning
confidence: 99%
“…In recent publications [13,32,33], the authors developed a technique to seasonally estimate the influence of instantaneous air density changes on the capacity factor of a given turbine. Floors et al [34] emphasized, like us, the importance of air density, and also used ERA5 to study its effects. In this sense, the main physical magnitude that synthesizes the influence of wind speed with air density is the wind power density, the main parameter used for map representation of offshore wind energy in this work for Lebanon.…”
Section: Introductionmentioning
confidence: 93%